PRAKTIK BAY'US SALAM DI MASYARAKAT KELURAHAN MAKARTI JAYA KABUPATEN BANYUASIN SUMATERA SELATAN (Kajian Living Hadis) - rica, rica; Hasanah, Uswatun; Nadhiran, Hedhri (The Hadith Department, Faculty of Ushuluddin and Islamic Thought, State Islamic University of Raden Fatah Palembang., 2023)
Abstract This paper aims to find out how the concept of bay'us salam in the hadith of the Prophet, as well as how the practice of bay'us salam is carried out by the community in Makarti Jaya Village and what is the motivation of the community in doing bay'us salam. This research is a qualitative research with the study of living hadith and uses social theory, namely the ERG motivation theory. Based on the research that has been carried out, it was found that first, the concept of bay'us salam in the hadith of the Prophet is a sale and purchase whose properties are mentioned, while the goods are still under the responsibility of the seller, and the delivery is at the agreed time. Second, bay'us salam carried out by the people of Makarti Jaya Village has experienced several developments such as the existence of DP money as a payment system. Third, people's motivation to do bay'us salam is influenced by several factors including geographical location, mutual assistance, traditions, fulfillment of needs and following trends. Keywords: Motivation, Bay‘us Salam, Hadith Abstrak Tulisan ini bertujuan untuk mengetahui bagaimana konsep bay‘us salam dalam hadis Nabi, serta bagaimana praktik bay‘us salam yang dilakukan masyarakat di Kelurahan Makarti Jaya dan apa motivasi masyarakat dalam melakukan bay‘us salam tersebut. Penelitian ini merupakan penelitian kualitatif berupa kajian living hadis dengan menggunakan teori motivasi ERG sebagai alat analisis. Berdasarkan penelitian yang telah dilakukan, ditemukan bahwa pertama, konsep bay‘us salam dalam hadis Nabi merupakan jual beli yang disebutkan sifat-sifatnya, sedangkan barang tersebut masih dalam tanggungan penjual, dan penyerahannya pada waktu yang telah disepakati. Kedua, bay‘us salam yang dilakukan oleh masyarakat Kelurahan Makarti Jaya mengalami beberapa perkembangan seperti adanya uang DP sebagai sistem pembayaran. Ketiga, motivasi masyarakat melakukan bay‘us salam dipengaruhi oleh beberapa faktor diantaranya yaitu letak geografis, saling bantu, tradisi, pemenuhan kebutuhan dan mengikuti trend.